The syntax of negative imperatives in Yemeni Arabic: A phase approach - Shormani, Mohammed Q; Alhussen, Fahad Saud (Cogent arts & humanities, 2024)
Negative imperatives in general have received less research compared to positive imperatives cross-linguistically, which is perhaps due to their complex nature. This article studies Yemeni Arabic (YA) negative imperatives, probing their syntactic and discourse properties, and proposing a syntax–discourse interface amalgamated with phase approach to the analysis of these structures. Syntactically, negative imperative structures in YA are bipartite in nature, consisting of the preverbal negative particle lā and the postverbal negative suffix – š, thus paralleling negative imperatives in French, for instance. We propose that the head Neg is split into NegP and NegClP as a result of Agree and interface properties between syntax and discourse. NegP is represented by lā and –š represents NegClP (=Clitic Negative Phrase). NegClP ensues from the clitic nature of –š. We also argue that the thematic subject of imperatives is a 2 (person) pro. Discoursally, we argue that the overt (pro)nominal constituent showing up preverbally is not a subject, but rather a C-domain element, precisely a topic. The latter merges in Spec,TopP and pro in Spec,vP, coreferentially correlated at the syntax–discourse interface, where coreferentiality takes the form of Agree as Match, which results in full interpretation of pro. The proposal accounts straightforwardly and elegantly for the bipartite negative imperative facts in YA, and other modern Arabic varieties. It has also adequately been applied to English and French, and hopefully, it can be applied cross-linguistically.